Mainstreaming climate risk management in development progress and lessons learned from ADB experience in the pilot program for climate resilience. (Metro Manila, Philippines Asian Development Bank, 2017)
he PPCR is a funding window of the Climate Investment Funds, of which ADB is a major partner in Asia and the Pacific, delivering investments through six country programs (Bangladesh, Cambodia, Nepal, Papua New Guinea, Tajikistan, and Tonga) and one regional program for the Pacific. This study looks back at the development of PPCR funding from an ADB perspective, documents the contributions of the PPCR to country readiness for adaptation planning and climate finance, and identifies some early lessons learned from Cambodia, Nepal, and Tajikistan.
Keywords: Climatic changes -- Management -- Developing countries; Climatic changes -- Government policy; Natural disasters -- Economic aspects -- Developing countries; Electronic books